Weighted Morrey Estimates for Multilinear Fourier Multiplier Operators - Songbai Wang; Yinsheng Jiang; Peng Li (Abstract and Applied Analysis)
The multilinear Fourier multipliers and their commutators with Sobolev regularity are studied. The purpose of this paper is to establish that these operators are bounded on certain product Morrey spaces Lp,k(ℝn). Based on the boundedness of these operators from Lp1(ω1)×⋯×Lpm(ωm) to Lp(∏j=1m‍ωp/pj), we obtained that they are also bounded from Lp1,k(ω1)×⋯×Lpm,k(ωm) to Lp,k(∏j=1m‍ωp/pj), with 0<k<1, 1<pj<∞, 1/p=1/p1+⋯+1/pm, and ωj∈Apj,j=1,…,m.